Interventions to increase physical activity in disadvantaged communities: A review of behavioural mechanisms - Laura Gormley; Cameron A. Belton; Pete Lunn; Deirdre A. Robertson (The Economic and Social Research Institute (ESRI), 2019)
Physical inactivity is now a significant driver of health and social inequalities among socioeconomically disadvantaged communities and poses a major challenge to policymakers, worldwide. Although a vast amount of research has focused on designing and evaluating interventions to increase physical activity, there remains little consensus on which interventions are likely to work. In this narrative review, we build on previous reviews by not only examining what interventions tend to work but by trying to understand why certain interventions tend to work, while others do not, through the lens of behavioural science. We present a behavioural framework through which the existing body of physical activity research could be viewed, in order to identify potentially effective mechanisms that would be likely to work in their intended domain. Our analysis finds that while there is evidence that the physical and educational environment matter for increasing levels of physical activity, interventions are more likely to be successful where they involve a social component. We conclude that a behaviourally informed physical activity intervention would thus employ a set of focused educational and socially-mediated behavioural mechanisms, within an appropriate physical environment.
Keywords: 330